Prescribing unapproved medical devices? The case of DIY artificial pancreas systems. (March 2021) - Roberts, Joseph T.F.; Moore, Victoria; Quigley, Muireann
In response to slow progress regarding technological innovations to manage type 1 diabetes, some patients have created unregulated do-it-yourself artificial pancreas systems (DIY APS). Yet both in the United Kingdom (UK) and internationally, there is an almost complete lack of specific guidance – legal, regulatory, or ethical – for clinicians caring for DIY APS users. Uncertainty regarding their professional obligations has led to them being cautious about discussing DIY APS with patients, let alone recommending or prescribing them. In this article, we argue that this approach threatens to undermine trust and transparency. Analysing the professional guidance from the UK regulator – the General Medical Council – we demonstrate that nothing within it ought to be interpreted as precluding clinicians from initiating discussions about DIY APS. Moreover, in some circumstances, it may require that clinicians do so. We also argue that the guidance does not preclude clinicians from prescribing such unapproved medical devices.